The ‘One Day Ten Greetings’ Movement (GERTUSAM) as a Strategy for Fostering Students’ Religious Character - Anna Roihatul Karomah; Syuhud (Al-Qalam Institue, 2026)
This study aims to examine the implementation and implications of the “One Day Ten Greetings” Movement (GERTUSAM) as a strategy to instill religious character among students. Employing a qualitative research design with a phenomenological approach, the study collected data through non-participant observations, semi-structured interviews with school staff, teachers, students, and parents, as well as documentary analysis of program records and materials. Findings reveal that GERTUSAM is systematically implemented through early introduction, consistent repetition, strict supervision, and the transition from mechanistic behavior to voluntary self-awareness. The program effectively fosters students’ religious character across three domains: spiritual, by enhancing mindfulness of God and reinforcing prayer routines; social, by promoting politeness, empathy, and cooperative behavior; and personal, by cultivating honesty, discipline, and responsibility. These outcomes demonstrate that structured habitual practices can facilitate internalization of moral and religious values, supporting ethical development. The study implies that school-based interventions like GERTUSAM provide a replicable model for cultivating disciplined, socially responsible, and spiritually conscious youth, informing educational policy and curriculum design